2013
DOI: 10.3746/pnf.2013.18.1.060
|View full text |Cite
|
Sign up to set email alerts
|

Spherical Granule Production from Micronized Saltwort (Salicornia herbacea) Powder as Salt Substitute

Abstract: The whole saltwort plant (Salicornia herbacea) was micronized to develop the table salt substitute. The micronized powder was mixed with distilled water and made into a spherical granule by using the fluid-bed coater (SGMPDW). The SGMPDW had superior flowability to powder; however, it had low dispersibility. To increase the dispersibility of SGMPDW, the micronized powder was mixed with the solution, which contained various soluble solid contents of saltwort aqueous extract (SAE), and made into a spherical gran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 30 publications
1
15
0
1
Order By: Relevance
“…The efficacy of S. herbacea against oxidative stress, inflammation, diabetes, asthma, hepatitis, cancer, gastroenteritis has already been reported [15]. Additionally, the powder of S. herbacea has been transformed into spherical granules showing the potential to be used as dietary NaCl [16]. S. herbacea has also proved that seed oil is stable to oxidation and eligible to be used in food processing [17].…”
Section: Introductionmentioning
confidence: 99%
“…The efficacy of S. herbacea against oxidative stress, inflammation, diabetes, asthma, hepatitis, cancer, gastroenteritis has already been reported [15]. Additionally, the powder of S. herbacea has been transformed into spherical granules showing the potential to be used as dietary NaCl [16]. S. herbacea has also proved that seed oil is stable to oxidation and eligible to be used in food processing [17].…”
Section: Introductionmentioning
confidence: 99%
“…Other authors have found that these plants can be used as a source of salt for several dishes. Indeed, S. herbacea powder can be transformed into spherical granules, which may be used as NaCl [85].…”
Section: Discussionmentioning
confidence: 99%
“…Extensive research has focused on the development of salt substitutes or replacements in meat products . There are three approaches for reducing the salt content of meat products: first, the use of a salt substitute such as potassium chloride (KCl), calcium chloride (CaCl 2 ), or magnesium chloride (MgCl 2 ); second, the use of flavor enhancers that do not have a salty taste, but enhance the saltiness of products when used in combination with salt; and third, the use of a mixture containing natural substances including herbs and/or plants . Sodium substitutes (KCl, MgCl 2 , and CaCl 2 ) have functional properties similar to those of NaCl but addition to meat products is limited by the bitter taste they produce .…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9] There are three approaches for reducing the salt content of meat products: first, the use of a salt substitute such as potassium chloride (KCl), calcium chloride (CaCl 2 ), or magnesium chloride (MgCl 2 ); second, the use of flavor enhancers that do not have a salty taste, but enhance the saltiness of products when used in combination with salt; and third, the use of a mixture containing natural substances including herbs and/or plants. [10][11][12] Sodium substitutes (KCl, MgCl 2 , and CaCl 2 ) have functional properties similar to those of NaCl but addition to meat products is limited by the bitter taste they produce. [13][14][15] Herbs and plants may be a safer and healthier alternative, as herbs have additional benefits including maintaining gastrointestinal function, improving cardiovascular health, and improving cholesterol control.…”
Section: Introductionmentioning
confidence: 99%